BRIDGING ACADEMIA AND INDUSTRY: A SYSTEMATIC LITERATURE REVIEW OF SOFTWARE ENGINEERING EDUCATION APPROACHES AND THEIR EFFECTIVENESS - Aliyah Aliyah; Asro Asro; Achmad Rozi; M. Adhit Dwi Yuda (Prosiding Amal Insani Foundation, 2026)
The gap between academia and industry remains a major challenge in software engineering education. Rapid technological change requires graduates to possess not only strong theoretical knowledge but also practical competencies, collaboration skills, and familiarity with real software development practices. This study presents a Systematic Literature Review (SLR) examining educational approaches used to bridge the academia-industry gap in software engineering education. A total of 54 scientific articles published between 2015 and 2024 were reviewed through a structured selection process based on PRISMA principles. The review focuses on curriculum design, project-based learning, agile-based education, industry collaboration, capstone projects, internships, and competency-based assessment. The findings show that project-based learning, agile learning, industry partnerships, and internship programs are the most frequently used approaches to improve students' readiness for professional roles. However, challenges remain in aligning university learning outcomes with rapidly changing industry expectations, particularly regarding practical experience, soft skills, and exposure to real tools and workflows. This article provides recommendations for strengthening software engineering education through adaptive curricula, stronger industry involvement, and continuous competency-based evaluation.